"Press On, Continue On": Rural Parents' Experiences of Transitions Within Early Intervention. (December 2022) - Decker, Kalli B.; Feigel, Alexandra J.; Foster, Tricia D.; Kepl, Rachel L.
Although all families experience a variety of transitions over time, families of children with exceptionalities tend to encounter more transitions during their children's earliest years. Transitions can be stressful and often include changes as part of early intervention or special education services. It is important to understand these transitions because the support families receive can influence child and family well-being. Therefore, we interviewed parents ( N = 28) across a rural U.S. state about their experiences of transition over time. Using thematic analysis, three common themes emerged: (a) change is constant, (b) positive relationships support changing needs and priorities, and (c) parents need more support, information, or access to services or providers. Parents reported relationships and collaboration with providers to be important, yet insufficient, in supporting transitions. Rurality added some challenges to parents' experiences with transition. Recommendations include empowering families, providing more access and/or removing barriers to services, and building family efficacy through family-focused services.